Discovery-Inquiry Learning Model Improves Physical Activity Learning Outcomes in View of Learning Motivation - I Dewa Made Suwika Antara; Wahjoedi; Swadesi, I Ketut Iwan (Universitas Singaperbangsa Karawang, 2024)
This study aimed at identifying and analyzing the effect of the discovery-inquiry learning model and learning motivation on the learning outcomes of physical activity. This study was an experimental research using the posttest only control group design. The population in this study were the eleventh grade of SMA Negeri 1 Tabanan in the academic year of 2021/2022 consisting of eleven classes. The study used simple random sampling. By using this sampling technique two classes were used as the experiment group and the other two classes as the control group. The data obtained was analyzed with two-way variance analysis, continued with the Tukey test to determine which groups were better than the other. The result showed that: (1) learning outcomes of physical activity of students who studied the discovery-inquiry learning model was better than students who studied the direct instruction model ( A1 = 35,188 > A2 = 34,250; F = 4,469; Sig. < 0,05); (2) there was an interaction between the learning model and learning motivation on the learning outcomes of physical activity (F = 36,728; Sig. < 0,05); (3) learning outcomes of students who studied with the discovery-inquiry learning model was better than students who studied with the direct instruction model of students with high learning motivation ( A1B1 = 38,83 > A2B1 = 35,21; Sig. < 0,05); and (4) learning outcomes of students who studied with the discovery-inquiry learning model was lower than students who studied with the direct instruction model of students with low learning motivation ( A1B2 = 31,54 < A2B2 = 33,29; Sig. < 0,05). Keywords: discovery-inquiry, physical activity, learning outcomes, learning motivation